Impacts of Work Connectivity During Non-Office Hours on Employee’s Attitudes and Behaviors: A Comparative Case between General Staffs and Executives in Educational Institutions in Shandong Province, China - Xiangzhi, Chen; Submahachok, Pattsornkun (Rajapark Journal, 2025)
This study investigates the impact of work connectivity during non-office hours on the attitudes and behaviors of general staff and executives in educational institutions in Shandong Province, China. Utilizing the Conservation of Resources (COR) theory and the Job Demand-Resource (JD-R) model, the research assesses the influence of digital work connectivity on various outcomes such as role overload, quality of work life, employee engagement, and counterproductive work behavior. A survey was conducted, and data from 626 valid questionnaires were analyzed using SPSS and AMOS software. The results indicated that work connectivity during non-office hours positively influences role overload and counterproductive work behavior, while it negatively affects the quality of work life and employee engagement for both general staff and executives. However, the impact was more pronounced in general staff. The study also found that information technology and high identity awareness had different impacts on work connectivity during non-office hours for the two groups. The research concludes that while work connectivity is inevitable, its management is crucial to mitigate its negative effects on employees. The study provides insights for policymakers and managers to better understand and manage the implications of work connectivity outside regular working hours.